2019
DOI: 10.1038/s41598-019-46696-6
|View full text |Cite|
|
Sign up to set email alerts
|

De novo assembly of the Platycladus orientalis (L.) Franco transcriptome provides insight into the development and pollination mechanism of female cone based on RNA-Seq data

Abstract: For seed-bearing plants, the basis of seed and fruit formation is pollination. The normal progression of pollination is through advances in continuous signal exchange and material transfer, which occur mainly in female reproductive organs; thus, the molecular mechanism of development in female reproductive organs is vital for understanding the principle of pollination. However, molecular biology studies on the development of female cones related to pollination are rare and unclear in gymnosperms, especially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…For seed-specific genes, seven significant enriched GO term, including GO:0004867 (serine-type endopeptidase inhibitor activity), GO:0045735 (nutrient reservoir activity), GO:0002020 (protease binding), GO:0004866 (endopeptidase inhibitor activity), GO:0030414 (peptidase inhibitor activity), GO:0061134 (peptidase regulator activity), and GO:0061135 (endopeptidase regulator activity) were screened out, which all play roles in seed aging [ 90 ], storage proteins [ 91 ], seed germination under salt stress [ 92 ], and different nitrogen levels [ 93 ]. GO:0030570 (pectate lyase activity) and GO:0016837 (carbon-oxygen lyase activity, acting on polysaccharides) had been screened out in the flower-specific genes in the process of pigmentation in the petals [ 94 ], petal abscission [ 95 ], female cone development, and pollination mechanism [ 96 ]. The GO enrichment analysis demonstrated that the predicted tissue-specific genes have unique functions consistent with the tissue they were expressed in, with similar results also declared in a previous study [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For seed-specific genes, seven significant enriched GO term, including GO:0004867 (serine-type endopeptidase inhibitor activity), GO:0045735 (nutrient reservoir activity), GO:0002020 (protease binding), GO:0004866 (endopeptidase inhibitor activity), GO:0030414 (peptidase inhibitor activity), GO:0061134 (peptidase regulator activity), and GO:0061135 (endopeptidase regulator activity) were screened out, which all play roles in seed aging [ 90 ], storage proteins [ 91 ], seed germination under salt stress [ 92 ], and different nitrogen levels [ 93 ]. GO:0030570 (pectate lyase activity) and GO:0016837 (carbon-oxygen lyase activity, acting on polysaccharides) had been screened out in the flower-specific genes in the process of pigmentation in the petals [ 94 ], petal abscission [ 95 ], female cone development, and pollination mechanism [ 96 ]. The GO enrichment analysis demonstrated that the predicted tissue-specific genes have unique functions consistent with the tissue they were expressed in, with similar results also declared in a previous study [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the promoter region contributed to the agronomic traits of plants [ 100 , 101 , 102 , 103 ]. By using CRISPR-Cas9, promoter editing was successfully applied to crop genetic improvements [ 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Together with being controlled at the transcriptional level, gene expression was also regulated at the post-transcriptional level, such as methylation [ 108 ].…”
Section: Discussionmentioning
confidence: 99%